2021
DOI: 10.3389/fphar.2021.752194
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Neutraligand for CXCL12/SDF-1α With Beneficial Regulatory Functions in MRL/Lpr Lupus Prone Mice

Abstract: Dysregulation of CXCL12/SDF-1-CXCR4/CD184 signaling is associated with inflammatory diseases and notably with systemic lupus erythematosus. Issued from the lead molecule chalcone-4, the first neutraligand of the CXCL12 chemokine, LIT-927 was recently described as a potent analogue with improved solubility and stability. We aimed to investigate the capacity of LIT-927 to correct immune alterations in lupus-prone MRL/lpr mice and to explore the mechanism of action implemented by this small molecule in this model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The number of leukocytes in mice with SLE significantly decreased and inflammation remarkedly improved after LIT-927 administration. 134 The studies on CXCR4 antagonists indicated that CXCR4 was a promising drug target for treating lupus. 135…”
Section: Lupus Erythematosusmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of leukocytes in mice with SLE significantly decreased and inflammation remarkedly improved after LIT-927 administration. 134 The studies on CXCR4 antagonists indicated that CXCR4 was a promising drug target for treating lupus. 135…”
Section: Lupus Erythematosusmentioning
confidence: 99%
“…Notably, LIT‐927, a small‐molecule compound derived from chalcone‐4‐p (Figure 1), also effectively blocked the CXCR4/CXCL12 axis in SLE by binding to CXCL12 instead of directly interacting with CXCR4. The number of leukocytes in mice with SLE significantly decreased and inflammation remarkedly improved after LIT‐927 administration 134 . The studies on CXCR4 antagonists indicated that CXCR4 was a promising drug target for treating lupus 135 …”
Section: Cxcr4/cxcl12 Axis–mediated Inflammatory Diseasesmentioning
confidence: 99%